2019
DOI: 10.1093/jamia/ocz032
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health information technology on the management and follow-up of test results – a systematic review

Abstract: Objective To investigate the impact of health information technology (IT) systems on clinicians’ work practices and patient engagement in the management and follow-up of test results. Materials and Methods A search for studies reporting health IT systems and clinician test results management was conducted in the following databases: MEDLINE, EMBASE, CINAHL, Web of Science, ScienceDirect, ProQuest, and Scopus from January 1999 to June 2018. Test results follow-up was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 74 publications
(158 reference statements)
0
21
0
1
Order By: Relevance
“…Electronic health records (EHRs) hold promise for facilitating follow-up of abnormal results, but research indicates that EHRs alone are insufficient to improve care quality. 1 Studies have shown that follow-up is similar in systems with and without EHRs 2,3 for electronically acknowledged and unacknowledged result alerts, 4 and that delays longer than 30 days occur even for "high-priority" EHR alerts. 4 Additionally, EHRs may create new challenges for managing results due to a high volume of alerts and notifications to physicians.…”
mentioning
confidence: 99%
“…Electronic health records (EHRs) hold promise for facilitating follow-up of abnormal results, but research indicates that EHRs alone are insufficient to improve care quality. 1 Studies have shown that follow-up is similar in systems with and without EHRs 2,3 for electronically acknowledged and unacknowledged result alerts, 4 and that delays longer than 30 days occur even for "high-priority" EHR alerts. 4 Additionally, EHRs may create new challenges for managing results due to a high volume of alerts and notifications to physicians.…”
mentioning
confidence: 99%
“…This represents an additional workload undertaken by clinicians to perform dual acknowledgment in the inbox and patient’s notes, providing further evidence of the impact of electronic test results management activities and notifications on clinician’s workload. 9 , 51 , 55 The need for visibility among the clinical team of actions taken after reviewing results represents a challenging area of great importance for the development of safe and effective HIT systems. Through exploring WAD, additional workload was also identified as a challenge faced by advanced nursing staff with ordering rights who practice autonomously in managing test results in the absence of an EMR inbox (theme 5).…”
Section: Discussionmentioning
confidence: 99%
“…HIT plays an increasing role in the management of diagnostic test results. A wide variety of HIT-enabled interventions 9 have been designed to assist clinicians in managing test results, including computerized physician order entry, 10 electronic results acknowledgment, 11–14 automated email notifications of TPADs, 2 , 3 and electronic health record (EHR) alerts. 15 , 16 Evaluations of HIT interventions have reported improvements in awareness, communication, and access to clinical test results, 4 , 11 , 14 as well as in efficiency, response time, and the proportions of tests being followed up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The majority of articles examined in these systematic reviews have focussed on clinician-centred strategies or interventions with only two reviews reporting studies of patient involvement in test-results follow-up, principally in relation to online access to test-results via the Internet, 7 patient portals 10 or personal health records. 10 As the recipients of diagnostic testing, patients have a vested interest in the effective management and communication of their test-results. Furthermore, it is recognized that patients requesting or reviewing results may serve as a safety net for missed test-results.…”
Section: Follow-upmentioning
confidence: 99%